Emergence of Drug-Resistant Pathogens in a Neonatal Intensive Care Unit - Aydınlı, Aydın; Sertel Şelale, Deniz; Kaya, Ayşe Demet (Journal of Pediatric Infectious Diseases, 2023)
Objective Neonatal bloodstream infections (BSIs) due to drug-resistant pathogens are a major cause of neonatal morbidity and mortality. Unfortunately, data regarding the pathogens and their resistance profile are limited in developing countries. The aim of this study was to determine the bacteriological profile and antimicrobial susceptibility patterns in neonatal BSI at a university hospital in Türkiye.Methods Medical records of neonates with suspected sepsis were retrospectively reviewed during the study period (between January 1, 2018, and December 31, 2020) for demographic data, blood culture, and antimicrobial susceptibility test results.Results During the study period, 117 BSI episodes were encountered in 106 neonates. The most common pathogen isolated was Staphylococcus epidermidis (n = 86, 73.5%), followed by Klebsiella pneumoniae (n = 11, 9.4%). Methicillin resistance among staphylococci (77/93, 82.8%) and extended-spectrum beta-lactamase (ESBL) production among Enterobacterales (14/17, 82.4%) were common. Gentamicin resistance was detected in 70.1% (54/77) of methicillin-resistant staphylococci and 78.6% (11/14) of ESBL (+) Enterobacterales. Vancomycin and colistin resistance were not detected.Conclusion The high rate of resistant pathogens encountered in neonatal BSIs underline the importance of constant surveillance of the local pathogens and their antimicrobial susceptibility patterns, which is crucial for implementing appropriate therapy that could save lives and lower the burden of antimicrobial resistance.
Keywords: bloodstream infection; neonatal sepsis; blood culture; antibiotic resistance; neonatal ICU